Synthesis and Characterization of New Azo Compounds Linked to 1, 8-Naphthalimide and Studying Their Ability as Acid-Base Indicators - Al-Majidi, Suaad M.H.; Al-Khuzaie, Mohammed G.A (Iraqi Journal of Science, 2019)
New Azo compounds containing an 1,8-naphthalimide moiety were synthesized from 1, 8-naphthalic anhydride by a reaction with p-phenylenediamine or benzidine to produce 1,8-naphthalimide derivatives (1 or 2), which were converted to diazonium salt derivatives by using sodium nitrite and acetic acid at 0-5 áµ’C. The diazonium salt was subjected to a coupling reaction with different substituted phenol in alkaline media at 0-5 áµ’c to produce azo compound derivatives (3-14).The New Azo compound derivatives (3-14) were identified by 1H-NMR, 13C-NMR, and FTIR and by measuring characteristic physical properties and specific reactions. Also, the ability of the prepared azo compounds to work as acid-base indicator was investigated, since azo dyes have different and sharp colors in acidic or basic solutions.